A systematic review of patient-practitioner communication interventions involving treatment decisions. Issue 2 (February 2017) - Grady, Alice; Carey, Mariko; Bryant, Jamie; Sanson-Fisher, Rob; Hobden, Breanne
Highlights: Communication interventions involving treatment decisions were examined. Few interventions were identified, none examined emergency treatment decisions. Included interventions have a high risk of bias and are poorly reported. It is imperative that an evidence-base is developed to inform clinical practice. Abstract: Objectives: To examine the: 1) methodological quality of interventions examining strategies to improve patient-practitioner communication involving treatment decisions; 2) effectiveness of strategies to improve patient-practitioner communication involving treatment decisions; and 3) types of treatment decisions (emergency/non-emergency) in the included studies. Methods: Medline, PsychINFO, CINAHL, and Embase were searched to identify intervention studies. To be included, studies were required to examine patient-practitioner communication related to decision making about treatment. Study methodological quality was assessed using Cochrane's Effective Practice and Organisation of Care risk of bias criteria. Study design, sample characteristics, intervention details, and outcomes were extracted. Results: Eleven studies met the inclusion criteria. No studies were rated low risk on all nine risk of bias criteria. Two of the three interventions aimed at changing patient behaviour, two of the five practitioner directed, and one of the three patient-practitioner directed interventions demonstrated an effect on decision-making outcomes. No studies examined emergency treatment decisions. Conclusions: Existing studies have a high risk of bias and are poorly reported. There is some evidence to suggest patient-directed interventions may be effective in improving decision-making outcomes. Practice implications: It is imperative that an evidence-base is developed to inform clinical practice.